KARAKTERISTIK KEMAMPUAN LITERASI STATISTIKA SISWA DALAM MENYELESAIKAN MASALAH MODEL PISA - Gunawan Gunawan; Nurhikmah Widi Asriani; Fitria Zana Kumala; Lukmanul Akhsani; Sri Rohmawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Statistical literacy skills have an essential role in various fields of life, one of which is education. This study describes students' statistical literacy skills in solving PISA model questions. This type of research is descriptive-qualitative. The research subjects were students of class VIII Junior High School. Collecting data in this study using tests and interviews. The purposive sampling technique was used to sample 6 students, categorized into three, namely high, medium, and low. Data analysis was carried out using the Mile and Huberman model consisting of data reduction, data presentation, and concluding. The results showed that students in the high and medium categories met all indicators of statistical literacy skills, namely understanding information, processing data, interpreting data, and evaluating. Students in the low category cannot master the evaluation indicators due to several internal factors.